High-quality changes of the pedagogical test "linear algebra, analytical geometry" - Lidiya A. Muratova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In this article according to the classical theory characteristics of validity and discriminative of the pedagogical test "Linear Algebra, Analytical Geometry" of a course of the higher mathematics of Samara State Technical University were estimated. Results of researches showed that all coefficients of correlation of tasks are with each other positive and don't surpass the size 0,3 that is considered a good indicator. Values of dot biserial coefficient of correlation of tasks with test point of the student changed. It influenced such characteristics of dough as a validity and a diskriminativnost. And, at last, by means of Pearson's criterion the positive result about normal distribution of test points is received.